Roman Bone Artefacts – First Steps Towards a New Approach - Hildegard Müller; Sabine Deschler-Erb; Dorota Wojtczak (EXARC Journal)
To date, archaeologists often use a typological approach to assess the functions of bone artefacts from the Roman period. In some of these assigned typological groups, certain artefacts do not have a clear definition. This study aimed to assess whether use-wear analysis combined with experimental archaeology could be applied to bone artefacts from the Roman period as an aid in identifying the function of these artefacts. Artefacts of the Roman site Augusta Raurica, Switzerland, were examined employing the use-wear approach and compared with experimentally reproduced and used replicas. These replicas were experimentally crafted from bone using lathes, files, knives, horsetail (Equisetum telmateia) and leather. During the experimental reproduction, many interesting observations about the different methods and raw materials were made. There was a significant difference observed between the use of cooked and raw bone material. The replicas of Roman bone artefacts were used on wax tablets made from wood and beeswax. They can produce legible letters on the wax and even left traces on the wood. The traces left on Roman bone artefacts' replicas were similar to two artefacts typologically classified as stili. This preliminary study produced some interesting results but also left many open questions in need of further examination.